2013
DOI: 10.1128/jcm.00346-13
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of the Epidemic Multiresistant Escherichia coli ST131 Clonal Group among Extended-Spectrum Beta-Lactamase-Producing E. coli Isolates in Copenhagen, Denmark

Abstract: We report the characteristics of 115 extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli clinical isolates, from 115 unique Danish patients, over a 1-year study interval (1 October 2008 to 30 September 2009). Forty-four (38%) of the ESBL isolates represented sequence type 131 (ST13)1, from phylogenetic group B2. The remaining 71 isolates were from phylogenetic groups D (27%), A (22%), B1 (10%), and B2 (3%). Serogroup O25 ST131 isolates (n ‫؍‬ 42; 95% of ST131) comprised 7 different K antigens, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
75
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 38 publications
15
75
1
Order By: Relevance
“…This might be explained by the lower number of average virulence factors expressed in ST131 isolates than in non-MDR strains (11). However, compared with other lineages of ESBL-producing E. coli isolates, ST131 strains were shown to carry a significantly higher number of virulence genes (9,13,14). The high metabolic potential of this lineage was recently suggested to contribute to its overall success (10,15).…”
mentioning
confidence: 86%
“…This might be explained by the lower number of average virulence factors expressed in ST131 isolates than in non-MDR strains (11). However, compared with other lineages of ESBL-producing E. coli isolates, ST131 strains were shown to carry a significantly higher number of virulence genes (9,13,14). The high metabolic potential of this lineage was recently suggested to contribute to its overall success (10,15).…”
mentioning
confidence: 86%
“…Only one strain (cat 6) contained the CTX-M-15 gene, and this strain belonged to ST131, presenting the typical characteristics of this sequence type, such as the presence of fyuA, iutA, kpsMII and malX, and allocation to the B2 phylogroup. 29 Over the last decade, the ST131 virulent pandemic clone has emerged in hospitals and in the community worldwide, causing outbreaks of MDR infections across the globe. 30 It has been frequently described as a urinary pathogen in humans, 31 and a fatal case of urosepsis associated with a multi-resistant strain of E. coli ST131 was reported recently 30 Although rarely isolated from companion animals, a recent report found E. coli ST131 to distribute among human and animal household members in Australia, suggesting serious clinical and public health implications.…”
Section: Discussionmentioning
confidence: 99%
“…Considering all sample types, the prevalence of E. coli ST131 among ESBL-producing E. coli isolates ranged from 22% (Spain) to 66% (United Kingdom) in Europe (mean value, 39% for five European countries) between 2006 and 2011 (20,72,75,96,139). The two studies conducted in Spain, 2 years apart at two hospitals in Galicia and Catalonia, indicated a marked increase in prevalence over this period: 22% in 2006 and 32% in 2008.…”
Section: Prevalence and Epidemiology Of E Coli St131 Among Human CLImentioning
confidence: 99%
“…E. coli ST131 strains are mostly of serotype O25:H4, with a specific O25 type, O25b. However, ST131 E. coli isolates of serotype O16:H5 have recently been identified in Japan, Denmark, Australia, Spain, Pakistan, and France (18)(19)(20)(21)(22)(23)(24). Moreover, some E. coli ST131 isolates have been shown to be nontypeable for O or H antigens (18,25).…”
Section: Bacterial Characteristicsmentioning
confidence: 99%